Numerical simulation of fly ash concrete under sulfate attack. (1st June 2015) - Nie, Qingke; Zhou, Changjun; Li, Huawei; Shu, Xiang; Gong, Hongren; Huang, Baoshan
Highlights: An existing numerical model was extended to accommodate fly ash effects. Pozzolanic and hydration reactions were included in the extended model. The extended model was validated with observation data from literature. Sulfate resistance of fly ash concrete was simulated using the extended model. Critical factors affecting concrete sulfate attack were explored. Abstract: Portland cement concrete (PCC) suffers sulfate attack in sulfate-rich environments. On the other hand, industrial by-products such as fly ash and slag are routinely added to PCC to improve its properties. However, the impact of fly ash on concrete durability is not always conclusive and it is time- and energy-consuming to test concrete durability in the laboratory or through field observation. This study presents a numerical simulation of the durability of Portland cement concrete made with fly ash. The simulation of sulfate attack on fly ash concrete was performed based on ion transport mechanism. The chemical reactions among chemical compounds of hydrated cement paste and sulfate ions were considered. Additionally, the pozzolanic and hydration reactions of fly ash were incorporated as well to incorporate the impact of fly ash. The pozzolanic and hydration reaction were simulated through the extended version of an existing numerical procedure. Field observation data from the United States Bureau of Reclamation (USBR) was employed to validate the extended simulation program. After pozzolanic and hydration reactions of fly ash were incorporated, the prediction agreed well with the field measurements. The simulation shows that pozzolanic reaction of fly ash can significantly slow down sulfate attack on concrete, thus increasing the sulfate resistance of PCC and extending the service life of concrete infrastructures. The major factors that affect the sulfate resistance of concrete were explored through the numerical simulation as well.